A comparative analysis of the tactics exerted by the Japanese gold medal judo winners at the 2004 Athens Olympics - Cho, S. Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The aim of the paper was to gain an understanding of the strategy modes usedted by the Japanese gold medal Judo winners at the 2004 Athens Olympics. The paper undertook a comparative analysis on the tactics, techniques and scoring of eight Japanese gold medal Judo winners with systematic observation analysis and event sampling methods through the use of video tapes. The research purposes were (1) to understand the individual exertion of tactics, techniques and the content of scoring among the eight Japanese Judo players, (2) to understand the differences of exertion of tactics, techniques and the content of scoring between genders, and (3) to understand the differences in the use of tactics, techniques and the content of scoring within their weight categories. Results / Discussion A one-way ANOVA on the differential test and the Scheffe post-hoc analysis was used to generate the following results: based on individual di fference of the eight Judo players, the differences induced from their use of tactics were in For-To Moving, Left-Right Moving (Side Moving,) Circling Moving (Circling by centering the opponent,) and Top Gripping; whereas from their application of technique, the differences were in Sutemi-Waza and Non-Gripping Attack (Attack without gripping the opponent`s rope;).From the content of their scores, the differences were in the Koka score, Yudo score, Waza-Ari score and First-minute score. Based on gender difference, the differences induced from their exertion of tactics were in Left-Right Moving and Circling Moving; whereas from their use of techniques, the differences were in Sutemi-Qaza; whereas from the content of their scorings, the differences were in the Koda score. Based on their weight difference, the differences induced from use of tactics were in Left-Right Moving (Side Moving) and B Section Attack; whereas from their use of techniques, the differences were in the Sutemi-Waza and Non-Gripping Attack. The differences in their application of tactics may rely on their individual gripping modes, techniques or their coaches experiences. However, there are still similarities on the exertion of tactics among the eight Japanese Judo winners. Their scoring time, which most often appears between the first and second minutes after a contest begins, concurs with their recent results. On the scoring ranks, Ippon appears most often, and O Waza is still the major attack strategy of the Japanese gold medal Judo winners. Lastly, on the scoring section, it is discovered the C section is favoured by Japanese winners.